Psychosocial work load and stress in the geriatric care - Dulon Madeleine; Gregersen Sabine; Schmidt Sascha G; Vomstein Martin; Nübling Matthias; Nienhaus Albert (BMC, 2010)
Abstract Background Due to the decrease in informal care by family members and the demographic development, the importance of professional geriatric care will rise considerably. Aim of this study was to investigate the psychosocial workplace situation for employees in this profession. Methods The German version of the COPSOQ (Copenhagen Psychosocial Questionnaire) was used for the assessment of psychosocial factors at work. The instrument includes 22 scales and 3 single items concerning demands, control, stress, support, and strain. Results between two study groups of geriatric care were compared to each other as well as to employees in general hospital care and a general population mean (COPSOQ database). Statistical analysis included t-tests, ANOVA and multiple comparisons of means. Statistical significance (p < 0.01, two-tailed) and a difference of at least 5 points in mean values were defined as the relevant threshold. Results In total 889 respondents from 36 institutions took part in the study. 412 worked in Home Care (HC), 313 in Geriatric Nursing Homes (GNH), 164 in other professions (e.g. administration). Comparison between HC and GNH showed more favourable values for the first group for the most scales, e.g. lower quantitative and emotional demands and less work-privacy conflict, better possibilities for development etc. Compared to external values from the German COPSOQ database for general hospital care (N = 1.195) and the total mean across all professions, COPSOQ-total (N = 11.168), the results are again positive for HC workers on most of the scales concerning demands and social support. The only negative finding is the very low amount of social relations at work due to the obligation to work alone most of the time. Employees in GNH rate predictability, quality of leadership and feedback higher when compared to general hospital care and show some further favourable mean values compared to the COPSOQ mean value for all professions. A disadvantage for GNH is the high rating for job insecurity. A supplementary subgroup analysis showed that the degree of negative evaluation of psychosocial factors concerning demands was related to the amount of working hours per week and the number of on-call duties. Conclusions Compared to employees in general hospital care and the COPSOQ overall mean value across all professions, geriatric care employees and especially home care workers evaluate their psychosocial working situation more positive for most aspects. However, this seems partly due to the very high proportion of part-time workers. Critical results for the two study groups are the relatively high job insecurity in nursing homes and the lack of social relations for the HCrs.